Overview of Sanitation Conditions in the Rubber Processing Industry of PT. XYZ - Saputra, Hendrik; Sulastri, Sulastri; Setiajaya, Arif (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2026)
Sanitation is a crucial aspect of the rubber processing industry because it plays a role in maintaining product quality, a clean work environment, and the health of workers. This study aims to describe the implementation of sanitation in the rubber processing industry at PT. XYZ, including sanitation of the work environment, sanitation of production processes and equipment, and sanitation of workers. The study used a descriptive method with an observational approach through direct observation, interviews, and documentation in the production area and supporting facilities. Data were analyzed qualitatively and descriptively in the form of narrative descriptions. The results indicate that PT. XYZ has implemented sanitation through routine cleaning of production areas, environmental management around the factory, cleaning of production equipment at every stage of the process, and the provision of personal protective equipment (PPE) for workers. However, sanitation implementation has not been optimal due to inconsistent use of PPE, incomplete cleaning of equipment, especially in hard-to-reach machine parts, and limited personal hygiene facilities such as handwashing stations and changing rooms in some work areas. Therefore, increased supervision, improved equipment cleaning methods, and the provision of more adequate sanitation facilities are needed to support a clean, safe work environment and support the quality of rubber products.